PENGARUH BANK INDONESIA TERHADAP PEREKONOMIAN INDONESIA - Fani Fitra; Shabrina Nailussaadah; Aprilliantoni, Aprilliantoni (Cahaya Ilmu Bangsa, 2024)
This study aims to analyze the influence of Bank Indonesia (BI) on the Indonesian economy. This research method uses qualitative methods and applies literature review methods. This study identifies various monetary policies implemented by BI and their impact on financial stability, economic growth, and the Indonesian financial system through a detailed literature review. The results of the study show that BI plays a central role in maintaining macroeconomic stability in Indonesia. Monetary policies implemented such as setting interest rates, open market operations, and maintaining foreign exchange reserves have proven effective in controlling inflation, maintaining the stability of the Rupiah exchange rate, and supporting sustainable economic growth. In addition to maintaining the stability of the financial system, BI also plays an active role in developing an efficient and comprehensive payment system.This study concludes that BI has successfully played its role as a monetary authority in maintaining the stability of the Indonesian economy. However, along with the increasingly complex challenges ahead, BI must continue to innovate and adapt in developing appropriate financial policies.